Simultaneous local excision of synchronous rectal polyps by transanal endoscopic microsurgery. Issue 1 (January 2020) - Issa, Nida; Fenig, Yaniv; Schmilovitz-Weiss, Hemda; Khatib, Muhammad; Nissim Bachar, Gil; Gingold-Belfer, Rachel; Yassin, Mustafa
Abstract : Background: The approach to surgical resection of multiple rectal lesions when endoscopic polypectomy is unsuccessful has historically been radical rectal resection with total mesorectal excision. This approach is fraught with high morbidity and mortality. We explored the possibility of performing one transanal endoscopic microsurgery procedure to resect multiple synchronous rectal lesions. Materials and methods: A retrospective analysis of all adult patients undergoing transanal endoscopic microsurgery at a single institution between 2004 and 2015. Clinical, demographic, and pathologic data were analyzed for all patients with synchronous rectal lesions that were excised via one transanal endoscopic microsurgery procedure. Results: Of the 158 patients who underwent transanal endoscopic microsurgery during the study period, 14 (8.8%) had two or more synchronous rectal lesions resected. The mean tumor size was 2.5 cm (range 0.5–3.5). The mean distance from the anal verge for the upper/proximal lesions: 10 ± 2.5 cm, and for the lower/distal lesions: 7 ± 2 cm. Mean operative time was 112 minutes (range 75–170). Median hospitalization time was 3 days (range 2–4). Two patients had urinary retention. No other complications were noted. All the transanal endoscopic microsurgery specimens were with clear margins. Conclusion: Transanal endoscopic microsurgery is a safe and feasible procedure for patients with multiple rectal lesions. We demonstrate no increase in surgical time, completeness of specimen resection, no increase in complications or hospital length or stay when compared to patients undergoing transanal endoscopic microsurgery for a single lesion.